cj0371: A Novel Virulence-Associated Gene of Campylobacter jejuni - Du, Xueqing; Wang, Nan; Ren, Fangzhe; Tang, Hong; Jiao, Xinan; Huang, Jinlin (Frontiers in Microbiology, 2016)
Campylobacter jejuni is the major cause of human bacterial diarrhea worldwide. Its pathogenic mechanism remains poorly understood. cj0371 is a novel gene that was uncovered using immunoscreening. There have been no previous reports regarding its function. In this study, we constructed an insertion mutant and complement of this gene in C. jejuni and examined changes in virulence. We observed that the cj0371 mutant showed significantly increased invasion and colonization ability. We also investigated the role of cj0371 in motility, chemotaxis and growth kinetics to further study its function. We found that the cj0371 mutant displays hypermotility, enhanced chemotaxis and enhanced growth kinetics. In addition, we localized the Cj0371 protein at the poles of C. jejuni by fluorescence microscopy. We present data that collectively significantly proves our hypothesis that cj0371 is a new virulence-associated gene and through the influence of chemotaxis plays a negative role in C. jejuni pathogenicity.